LEGAL STATUS OF BANK GUARANTEE ON BEHALF OF THIRD PARTIES IN BANKRUPTCY PERSPECTIVE - Hartini, Rahayu (Yustisia, 2017)
This study aimed to observe the legal status of the immovable that became a bank guarantee on behalf of third parties in the bankruptcy and whether the curator has the authority to insert objects that have been done Collateral guarantees which Foreclosed (hereinafter referred AYDA) prior to the bankruptcy decision boedel into bankruptcy.The method used is a normative research using three approaches: statute approach, conceptual approach, case approach, and analyzed "conten analysis". Based on the discussion of the results of research obtained the following conclusions: 1). The collateral property of a third party cannot be entered as boedel bankrupt debtor, as a third party guarantee is not a property of the Borrower; It is used as the basis of legal considerations (ratio decidendi) for the judges to decide the case of bankruptcy among Curator Albert Riyadi Suwono (applicant bankruptcy) with PT. Anglomas International Bank (AMIN BANK). 2). Curators do not have the authority to push objects of collateral that has been done AYDA prior to the bankruptcy decision into boedel bankrupt (pursuant to Article 56 Paragraph (1) the Bankruptcy Law that provides a period of suspension of execution rights guarantees security rights 90 (Ninety) days. In order not occur: legal norms are vague (vegen norm) and the conflict of norms and have an impact on the lack of legal certainty. Hence the need to revise the unprotected substrate of law No. 37 of 2004 on Bankruptcy and PKPU. Particularly with respect to Article 55 paragraph (1) and Article 56 paragraph (1).